What shapes parents' attitudes towards bilingual education? Evidence from Mozambique - Sara Alhola; Feliciano Chimbutane; Ritva Reinikka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
This qualitative study explores parental attitudes towards bilingual education in Mozambique. To improve foundational learning, several countries in sub-Saharan Africa have re-evaluated their language-ofeducation policies and experimented with bilingual education. Community buy-in is essential for a successful bilingual programme, particularly in contexts where former colonial languages retain socioeconomic prestige. Despite variation across schools, our findings, based on focus group discussions in Maputo and Nampula provinces, show that a majority of parents support bilingual education. Initial scepticism often shifted when observing their children learning to read. However, parents consistently expressed concerns about their children not learning adequate Portuguese, the most common reason for opposing bilingual education. Furthermore, parents lacked information about the rationale, practices, and benefits of bilingual education- for which a remedy would be the school providing full and regular information. Apart from parental buy-in (demand side), for a successful bilingual programme effective implementation (supply side) is indispensable to produce robust learning results-the most critical factor shaping parental attitudes.
Keywords: I21; I29; 330; bilingual education; language of instruction; parental attitudes; education policy; implementation; focus groups; Mozambique